An Analytical Approach To Challenges And Solutions In Higher Education Marketing Management In Indonesia - Dasep Supriatna (PT. Hasba Edukasi Mandiri, 2025)
This study provides an analytical overview of marketing management challenges and solutions within Indonesian higher education institutions (HEIs). Employing a qualitative, multiple case study approach guided by the Resource-Based View (RBV) and Relationship Marketing Theory, we analyzed data from interviews and institutional documents. Findings reveal significant challenges stemming from inadequate unique resources (RBV) and underdeveloped stakeholder relationships (Relationship Marketing). Effective solutions necessitate integrating resource development, such as enhancing brand reputation and digital capabilities, with strategies to build stronger connections with students, alumni, and industry partners.